Femtosecond studies: observing transition states and other ultra-short-lived species. (1st June 2016) - Kemp, Terence
To celebrate 2015 as the 'International Year of Light', this article offers a short survey of the progress made since the award of the Nobel Prize of 1999 to Professor Ahmed Zewail for his pioneering work on taking the timescale for observation of light-induced events down to the femtosecond level. Developments have included the extension of studies (i) to larger molecules, leading up to biological systems; (ii) the increased range of detection methods of transient species from the UV-Vis to the infrared region; (iii) the introduction of Raman spectroscopy to augment IR studies; (iv) examination of combination events to supplement dissociation events; (v) the interrogation of transient structures by X-ray absorption spectroscopy; (vi) the study of reactions taking place at solid surfaces.